Incorporation of metacognitive strategies in teaching writing to engineering students - Ismail, Iza Nurhidayah (2015)
Effective English writing has long been a challenge in English language teaching. Metacognition has provided another perspective for ESL writing. Metacognitive strategies include skills in planning, monitoring and evaluating which develop learners to become independent and capable of directing their own learning process and thus become eff~cientl earners. This pilot study investigates the problems encountered by engineering students in learning writing based on lecturers' perceptions. It also examines the effectiveness of using the selected metacognitive strategies in ESL writing. 70 participants were selected and categorized in two groups; control and experimental. Interviews were used to investigate the students' problems. Pre-test and post-test written essays were also used to examine the effgetiveness of metacognitive strategies implemented to the students. The interviews were transcribed verbatim for analysis while the data obtained fiom pre-test and post-test was analyzed by using Statistical Package for Social Sciences (SPS S).